Exploring the Experiences of Cambodian Labor Migrants: The Journey to Thailand under the Framework for Bilateral Agreements - Sakulsri, Teeranong; Nurick, Robert; Oeur, Il (Journal of Mekong Societies, 2020)
Over the past two decades, millions of people from Cambodia have migrated to Thailand. Much of this migration can be characterized as “irregular migration” as many of these migrants did not have proper legal documents or work permits. The Thai authorities have employed two parallel strategies for regularizing temporary migration to Thailand. The first has been to register migrant workers already in Thailand. The second has been to enter into bi-lateral MOUs with the Cambodian government. The present study explores these migrants’ experiences under the framework for bilateral agreements. Data were gathered through in-depth interviews with migrants, their family members, brokers, and recruitment agencies in four provinces in Cambodia. From this study, it is clear that an increasing number of migrants have become more aware of laws and regulations. However, there are major differences in the cost of formal and informal migration procedures. Formal procedures for migration between Cambodia and Thailand are relatively expensive, complex, time consuming, and based on networks. Some prospective migrants revealed that they have experienced being cheated in Cambodia during the processing of their documents. They did not have a complete understanding of each type of document and its purpose, and that is the reason they used passports with no work visas for working purposes. The findings of the study make clear that an investment in hands-on public awareness of documentation and trusted channels is needed so that prospective migrants and their families are fully informed before making the decision to migrate. There should be laws and standards in both the sending country and the receiving country (Thailand), specifying the costs and duration of the process to import labor, and this information should be publicly disseminated to the relevant offices/ agencies/personnel in both countries.